Spinous Process Osteochondroma as a Rare Cause of Lumbar Pain - Bárbara Rosa; Pedro Campos; André Barros; Samir Karmali; Esperança Ussene; Carlos Durão; João Alves da Silva; Nuno Coutinho (Case Reports in Orthopedics)
We present a case of a 5th Lumbar Vertebra (L5) spinous process osteochondroma as a rare cause of lumbar pain in an old patient. A 70-year-old male presented with progressive and disabling lower lumbar pain. Tenderness over the central and left paraspinal area of the lower lumbar region and a palpable mass were evident. CT scan showed a mass arising from the spinous process of L5. Marginal resection of the tumor was performed through a posterior approach. The histological study revealed an osteochondroma. After surgery, pain was completely relieved. After one year there was no evidence of local recurrence or symptoms. Osteochondromas rarely involve the spine, but when they do symptoms like pain, radiculopathy/myelopathy, or cosmetic deformity may occur. The imagiologic exam of election for diagnosis is CT scan. When symptomatic the treatment of choice is surgical resection. The most concerning complication of osteochondromas is malignant transformation, a rare event.